Clinical companion for medical-surgical nursing : concepts for interprofessional collaborative care.: concepts for interprofessional collaborative care. (2020) - Ignatavicius, Donna D; Workman, Linda; Rebar, Cherie R; Heimgartner, Nicole M
No abstract available